Interventions for Weight Regain after Bariatric Surgery - Muñoz, Rodrigo; Soto, Pedro (Digestive Disease Interventions, 2021)
Bariatric surgery is the most effective available treatment for obesity, inducing a significant and durable weight loss, and improving several obesity-associated diseases. However, as the number of bariatric surgeries performed increases, so does the prevalence of patients who experience either insufficient weight loss or weight regain, accompanied by relapse or the emergence of new obesity-related diseases. Endoscopic and surgical bariatric revisional procedures are used to promote weight loss and improve metabolic function to address these problems. After a psychological, nutritional, medical, and anatomical evaluation of the gastrointestinal anatomy has been completed, patient candidacy to a revisional procedure must be defined. In those patients with insufficient weight loss or weight regain associated with relapse, the emergence of new obesity-related diseases, or quality-of-life deterioration, a revisional procedure must be selected. Although current evidence comes mainly from observational and retrospective studies, with a limited number of patients and short follow-up times, the available data indicate that revisional procedures are useful to induce a significant weight loss and/or promote remission of obesity-associated diseases, albeit an increased risk of surgical and/or nutritional complications. Thus, careful selection of patients is needed to minimize risk and maximize the benefit of these procedures.
Keywords: bariatric surgery; weight regain; revisional surgery; interventions